Effect of urea and squaramide IMPDH inhibitors on C. parvum: in vitro trial design impacts the assessment of drug efficacy - Anne-Charlotte Lenière; Amit Upadhyay; Jérôme Follet; Timothy P. O'Sullivan (International Journal for Parasitology: Drugs and Drug Resistance)
The protozoan parasite Cryptosporidium is the etiological agent of cryptosporidiosis, a ubiquitous diarrheic disease affecting humans and animals. Treatment options are limited, highlighting an urgent need for novel therapeutics. Despite decades of research and a wide diversity of strategies to tackle parasite metabolic pathways, no completely effective drug has been identified to date. Within targeted parasite enzymatic and metabolic pathways, the synthesis of nucleotide mediated by the inosine 5′-monophosphate dehydrogenase (IMPDH) enzyme is the focus of significant research efforts. Based on our prior studies of bacterial IMPDH inhibitors, we report herein the development and characterisation of novel inhibitors targeting Cryptosporidium parvum IMPDH (CpIMPDH). Specifically, we synthesised heteroaryl-containing urea and squaramide analogues to evaluate their potential in vitro anti-Cryptosporidium activity. Initial screening identified nine active compounds with the most potent candidates achieving IC50 values as low as 2.2 μM. Subsequent time-course experiments revealed that the molecules effectively inhibit parasite invasion and early intracellular development but failed to tackle C. parvum growth when introduced at 30 h post infection. The present work introduces a new family of squaramide-derived IMPDH inhibitors and also interrogates the need to standardise commonly accepted protocols used for assessing anti-cryptosporidial drug activity.